Virtual reality hypnosis diminishes experimental cold pain and alters autonomic responses - Terzulli, Claire; Chauvin, Chloé; Champagnol Di-Liberti, Cédric; Faisan, Sylvain; Goffin, Laurent; Gianesini, Coralie; Graff, Denis; Dufour, André; Laroche, Edouard; Salvat, Eric; Poisbeau, Pierrick (Frontiers in Pain Research, 2023)
Immersive virtual reality (VR) is a promising tool to reduce pain in clinical setting. Digital scripts displayed by VR disposals can be enriched by several analgesic interventions, which are widely used to reduce pain. One of these techniques is hypnosis induced through the VR script (VRH) which is facilitated by immersive environment and particularly efficient even for low hypnotizable patients. The aim of this study is to assess the efficacy of a VRH script on experimentally induced cold pain perception (intensity and unpleasantness) and physiological expression. 41 healthy volunteers had been recruited in this within-subjects study. They received 9 stimulations of 20 seconds (3 non-nociceptive cold; 3 low nociceptive cold and 3 highly nociceptive cold) during a VRH session of 20 minutes (VRH condition) or without VRH (noVRH condition). Physiological monitoring during the cold pain stimulation protocol consisted of recording heart rate, heart rate variability and respiratory frequency. Maximum cold pain intensity perception, measured through the visual analog scale (VAS) on 10, was of 3.66±1.84 (VAS score/10) in noVRH condition and 2.46±1.54 in VRH (Wilcoxon, p<0.0001). Considering pain unpleasantness perception, 3.68±2.06 in noVRH and 2.21±1.63 in VRH (Wilcoxon, p<0.0001). Hypnotizability negatively correlated with the decrease in VAS intensity from noVRH to VRH (Spearman r=-0.45; p=0.0038). In our sample, we found that 31/41 volunteers (75.6%) displayed a reduction of more than 10% of their VAS pain intensity and unpleasantness scores. Trait anxiety was the best predictor of the VRH responders, as well as heart rate variability. In addition, respiratory rate was diminished under VRH in every subgroup. VRH is an effective tool to reduced pain intensity and unpleasantness in a vast majority of healthy subjects. We further indicate in this study that heart rate variability parameter RMSSD (root mean square of successive differences) is a good predictor of this effect, as well as anxiety as a personality trait (but not state anxiety). Further studies are expected to determine more precisely to whom it will be the most useful to offer tailored, non-pharmacological pain management solutions to patients.